The Development and Function of Serpentine/Sinusoidal Walls - Siegel, Oren.
This article discusses the meaning and origins of serpentine walls, also known as sinusoidal walls, an architectural form most commonly attested at Middle Kingdom sites, though examples are known from the New Kingdom as well. Following a review of previous interpretations of serpentine walling and a survey of examples of this architectural feature, this article will demonstrate that such walls did not possess a particular religious or ritual signicance, though this does not mean that they were devoid of symbolic meaning. Given their presence at domestic installations, marginal placement relative to temple or funerary monuments, and frequent association with unnished monumental constructions, the origins of serpentine walling should perhaps be sought in nonelite architectural practices. In view of the sites of where they were rst employed and last attested, serpentine walling seems may have been a regional Theban, or at least Upper Egyptian, building technique that was adopted for use by the Eleventh and Twelfth Dynasty kings and subsequently proliferated throughout Egyptian territory.